Escrevendo o movimento com a luz: a fotografia de dança questiona o fotojornalismo - Correa, Maria Inês Castro de Azevedo (2013)
The publication of photographs in the press midia follows patterns which understand that a journalistic photography registers a fact and should be faithful to it. The photography of dance slips away from such demand. And, if it really focus on its object (the dancing) in order to describe it faithfullly, it will be closer to the artistic photography, no longer following journalistic criteria. That is the hypothesis here proposed: the nature of the photography of dance could collaborate to update the rules reigning on the publication of images in cultural journalism. In some ways, every photo fragments time, and the photography of dance which works with body movements, cuts space and time. Having such singularity, the photography of dance the object of this research takes part in the images culture universe (BAITELLO, 2006). FLUSSER (2002), DUBOIS (2009), MACHADO (1984, 2010), BENJAMIN (1985) and SODRÉ (2009) will be considered during this research. The Bodymidia Theory (KATZ & GREINER, 2005, 2010, 2011) will be applied as an aggregative axis of the bibliography, in order to consolidate the theoretical fundaments according to which every communication originates from a body-environment relation; and in terms of photography of dance, such condition seems to be central. The methodology will begin reviewing the bibliography applied at studying the case of the blog www.corpoemimagem.blogspot.com, on which a very important part of the São Paulo city dancing productions performed between 2007 and 2012 has been randomly registered. Such photographs are treated as parts extracted from the cycle of happenings to which they belong. They are visual fragments of a six year period. To research the relation between photograph of dance and cultural photojournalism topics such as the photographer profile as a specialist, the photographic eye and the photographer s relation with what he does (SENNETT, 2009) will be prioritized